The Impact of Financial Market Volatility and Political Instability on Tourism Sector Performance Case Study on Major Tourism Destinations in Indonesia - Lesfandra, Lesfandra (Eastasouth Institute, 2024)
This study investigates the impact of financial market volatility and political instability on the performance of the tourism sector in major tourism destinations in Indonesia. Utilizing a quantitative research approach, data were collected from 180 respondents through a structured questionnaire employing a Likert scale. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 3. The findings indicate that both financial market volatility and political instability have positive and significant relationships with the performance of the tourism sector. These results suggest that despite the challenges posed by financial and political fluctuations, the tourism sector in Indonesia remains resilient and continues to thrive. The study highlights the importance of strategic planning, effective marketing, and continued investment in tourism infrastructure to sustain growth amidst financial and political uncertainties. These insights are valuable for policymakers and stakeholders in the tourism industry to enhance the robustness and sustainability of the sector.